Evolution of allograft fibrosis and function in kidney transplant recipients: a retrospective analysis of stable patients under CNI and mTORi - Becker, Luis Eduardo; Weritz, Bernhard Christoph; Xue, Yi; Groß-Weissmann, Marie-Luise; Waldherr, Rüdiger; Zeier, Martin; Sommerer, Claudia (Transplant international, 2015)
Histological evaluations of renal allograft biopsies are essential for diagnosis, but still show a low predictive value for long-term allograft function. One limitation relies on the fact that the analysis is usually based on a single biopsy sample, and therefore, no dynamic changes are considered. Using two distinct approaches, we evaluated the evolution of fibrosis and related markers in 36 stable kidney transplant patients under calcineurin inhibitor therapy with two indication biopsies each, prior and at least 6 months after substitution by mTORi (N = 18), or maintenance on CNI (N = 18). In the method comparison, both Banff chronicity score and the digitally assessed fibrosis were correlated with allograft function at biopsy (r = −0.36 and r = −0.72, P = 0.002 and P < 0.0001, respectively). However, only the progression of fibrosis digitally assessed was correlated with allograft function loss, not only within the time between biopsies (r = −0.47, P = 0.004) but also in the 60-month follow-up (r = −0.47, P = 0.006). In the group analysis, despite of a higher incidence of C4d positivity (P = 0.05), progression of fibrosis, TGF-β1 expression, and allograft function decline were significantly lower after conversion to mTORi compared with maintenance on CNI (P = 0.05, P = 0.02 and P = 0.01, respectively). PDGF, VEGF, b-FGF, and HIF1A expressions remained stable over time regardless of therapy.
Gesehen am 04.08.2020